Grounding what matters: a pluriversal lens for social values as a way to practice ecological democracy in Flood Risk Management - Seb O’Connor (Ecosystems and People)
Ecological democracy has drawn upon relational approaches through Indigenous thinking and pluriversal politics to re-imagine democratic design and practice. This presents an alternative paradigm through which to consider social values as a conceptual tool that can enact the kinds of sustainability transformations needed in contexts such as Flood Risk Management. In this article, I explore the potential of a pluriversal lens for social values as a way to perform ecological democracy by following the implications of (1) an expanded understanding of the social, (2) what it means to work with processes of change and (3) widening understandings of how values are generated. To understand a pluriversal lens in practice, I draw on a case study of a local beck restoration project in the UK. Through key methodological choices that challenged political logics of representation, social values emerged by grounding what mattered to people in their everyday material relations. This case study demonstrates the potential for a pluriversal design of social values methods to perform ecological democracy in ways that generate more convivial human–nature relationships.